Co-management or no management: The prospects for internal governance of common property regimes through dynamic contracts - Swallow, B.M.; Bromley, D.W. (Informa UK Limited, 1994)
It has been suggested that African rangelands would be utilized and managed on a more sustainable and profitable basis if they were governed by co-management arrangements, with state governments defining group rights and governing inter-group interactions and local organizations governing interactions among members within particular groups. In this paper we develop a discrete-time dynamic model of a rangeland to investigate the possibilities for internal management of resource use interactions within a common property regime. We find that there can be effective internal management without any formal institutional structure within the regime if: (1) group members are confident that the boundaries of the regime will be effectively protected; (2) the group of resources users is kept relatively small; (3) future pasture potential is not overly sensitive to changes in the current stocking rate; and (4) individuals do not discount future payoffs too heavily.